Dampak Teknologi Terhadap Prestasi Mahasiswa Unmaris - Krista Ismaya Holi; Haryance Umbu Dasa; Asron Turu Lalu Pengu; Yudis Bili (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Education for a nation that is currently developing like the Indonesian nation is currently an absolute necessity that must be developed in line with development demands step by step. Education that is managed in an orderly, orderly and efficient manner can produce something that is capable of accelerating the process of national civilization which is based primarily on creating general prosperity and the intelligent life of our nation, in accordance with the objectives of national education itself. The aim that researchers want to achieve in this research is to find out and describe the leadership style of school principals and work motivation in improving teacher performance at UNIVERSITAS STELLA MARIS SUMBA (UNMARIS). The data collection method is through distributing questionnaires to respondents directly. The respondents in this research were teachers at UNIVERSITAS STELLA MARIS SUMBA (UNMARIS)